Vanadium redox flow batteries: A comprehensive review. (October 2019) - Lourenssen, Kyle; Williams, James; Ahmadpour, Faraz; Clemmer, Ryan; Tasnim, Syeda
Highlights: Electrical energy storage with Vanadium redox flow battery (VRFB) is discussed. Design considerations of VRFBs are addressed. Limitations of each component and what has been/is being done to address said limitations are discussed. Critical research areas along with future development recommendations are highlighted. Abstract: Interest in the advancement of energy storage methods have risen as energy production trends toward renewable energy sources. Vanadium redox flow batteries (VRFB) are one of the emerging energy storage techniques being developed with the purpose of effectively storing renewable energy. There are currently a limited number of papers published addressing the design considerations of the VRFB, the limitations of each component and what has been/is being done to address said limitations. This review briefly discusses the current need and state of renewable energy production, the fundamental principles behind the VRFB, how it works and the technology restraints. The working principles of each component are highlighted and what design aspects/cues are to be considered when building a VRFB. The limiting determinants of some components are investigated along with the past/current research to address these limitations. Finally, critical research areas are highlighted along with future development recommendations.